The Symbolic Significance of the Landscape of Vilnius (Gediminas) Avenue from the Late Nineteenth Century to the Early Twenty-First Century in the Retrospective of Lithuanian Historical Policy (Relevant Tomorrow / Aktualu rytoj, 2023)
The present-day Gediminas Avenue (hereinafter, the Avenue) in Vilnius, which replaced the via sacra that ran from the Cathedral and the Palace of the Grand Dukes to the Gate of Dawn in the Middle Ages, became the most important urban artery of the Lithuanian capital in the late nineteenth century. It has remained so until today. The changes in its architectural form and toponymy, which have been reconstructed using various sources and historiography, testify to the growing political and symbolic significance of this street, depending on the political regimes that ruled Lithuania at the time and the particular ideologies they professed. The article examines the change in the symbolic landscape of the Avenue from the late nineteenth century to the early twenty-first century in the retrospective of Lithuanian historical politics, i.e., how it has reflected and continues to do so the memorial culture of the administrators of Lithuania, which justified their claim to the city. From the late nineteenth century until World War I, the creators of the Avenue—representatives of the Russian tsarist administration—shaped it visually and semantically on the model of the great cities of the Russian Empire, Moscow and St Petersburg. Subsequent foreign political regimes that took over Vilnius also sought to attach key symbols on the Avenue in order to justify their political legitimacy in the region and to link Lithuania to the grand historical narratives nourished by the “Center.” The most recent, post-Soviet, semantic transformation of the Avenue is the result of a deliberate attempt to form a unified and coherent national historical narrative. However, the narrative embodied in the spaces and objects of the Avenue does not, in fact, leave room for the interpretations of the past of other ethno-cultural communities of the capital that lived here, which can be found in other parts of Vilnius Old Town.
Keywords: images of Vilnius; Gediminas Avenue; public spaces; public monuments; toponymy; Lithuanian history policy